PENGARUH INOVASI INDIVIDU DAN PENDIDIKAN KEWIRAUSAHAAN TERHADAP NIAT BERWIRAUSAHA SOSIAL - Tara Pratiwi; Leny Noviani (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
This study aims to analyze two main issues: 1) the influence of individual innovation on social entrepreneurship intentions among students in the Economics Education Study Program, Faculty of Teacher Training and Education, Sebelas Maret University; 2) the influence of entrepreneurship education on social entrepreneurship intentions among the same student group. This study employed a quantitative approach using a survey method. The population included all active students from the 2021 and 2022 intakes. The sample size of 152 students was selected using proportional random sampling to ensure proportional representation from each intake. Data were obtained through questionnaires using a five-point Likert scale. In analyzing the data, the researchers first conducted classical assumption tests, including normality, linearity, multicollinearity, and heteroscedasticity tests, to ensure the feasibility of the regression model. Next, hypothesis testing was conducted using descriptive analysis, multiple linear regression, t-tests, and coefficient of determination calculations to determine the strength of each independent variable's influence on the dependent variable. The results indicate that both individual innovation and entrepreneurship education have a positive and significant influence on students' intentions to pursue social entrepreneurship. These findings confirm that internal factors such as the ability to innovate as well as external factors in the form of entrepreneurial learning play an important role in encouraging interest in social entrepreneurship among students.